The Implementation Of Motorcycle Junction Box To Reduce Motorcycle Accident Rate In Malaysia - Mohd Ali, Siti Najihah (Universiti Sains Malaysia, 2018)
Motorcycles are among the major causes of road accidents in most Asian countries road networks including Malaysia. This indicates that motorcyclists are among the most vulnerable road users throughout these networks. For the sake of motorcycle safety in Malaysia, this paper provides an overview of the implementation of motorcycle junction box in selected few road junctions in Kuala Lumpur City. This research paper investigated the implemented zone helping to reduce accident rates involving motorcycles by analysing the accessibility of the zone, it effectiveness and what are the awareness and acceptance level of the public towards the implementation of the zone. The methods for data collection are by using questionnaires as the primary data collection and secondary data is obtained from related government and private agencies. The results of analysing data showed that the implementation of the motorcycle zone was proven to be effective in reducing the motorcycle accident rate and the effectiveness of the zone is also achieved. About 42.7% of respondent are aware about the existed zone in selected areas and nearly 90% of them accepted that the implemented zones can help in reducing motorcycle accident rates in Malaysia.